Dietary Nutrients and Urinary Incontinence in Japanese Adults - Hirayama, Fumi; Lee, Andy (Wiley-Blackwell, 2012)
Objectives: To investigate the association between dietary nutrients and urinary incontinence (UI) among Japanese adults. Methods: A total of 1017 adults (710 men and 307 women) were recruited from the community in central and southern Japan. A structured questionnaire, incorporating the International Consultation on Incontinence Questionnaire-Short Form (ICIQ-SF) and a validated food frequency questionnaire, was administered to participants by face-to-face interview. Information on dietary nutrients intake from each food item was obtained using the Japanese food composition tables. Logistic regression analyses were performed to determine the association between nutrients intake and the prevalence of UI. Results: The observed prevalence of UI was 8.7% (n = 62) for men (mean age 62.5 years) and 29% (n = 89) for women (mean age 62.0 years) based on the ICIQ-SF criterion. Of the 50 dietary nutrients and micronutrients considered, soluble fiber (P = 0.03) and omega-6 polyunsaturated fatty acids (P = 0.01) were found to be inversely associated with the UI prevalence for men, whereas increasing the intake of lutein/zeaxanthin appeared to be marginally associated (P = 0.04) with a reduced risk of UI for women. Conclusion: Three dietary nutrients have been identified to be associated with UI in middle-aged and older Japanese adults. Further research and clinical trials are needed to ascertain the effects of dietary nutrients on UI.